Mechanotransductive N-cadherin binding induces differentiation in human neural stem cells - McKay Cavanaugh; Rebecca Kuntz Willits (Mechanobiology in Medicine, 2025)
The neural stem cell niche is a complex microenvironment that includes cellular factors, secreted factors, and physical factors that impact stem cell behavior and development. Cellular interactions through cadherins, cell–cell binding proteins, have implications in embryonic development and mesenchymal stem cell differentiation. However, little is known about the influence of cadherins within the neural stem cell microenvironment and their effect on human stem cell maintenance and differentiation. Therefore, the purpose of this study was to develop synthetic substrates to examine the effect of cadherin mechanotransduction on human neural stem cells. Glass substrates were fabricated using silane, protein A, and recombinant N-cadherin; we used these substrates to examine the effect of N-cadherin binding on neural stem cell proliferation, cytoskeletal structure and morphology, Yes-associated protein-1 (YAP) translocation, and differentiation. Bound exogenous N-cadherin induced concentration-dependent increases in adherens junction formation, YAP translocation, and early expression of neurogenic differentiation markers. Strong F-actin ring structures were initiated by homophilic N-cadherin binding, eliciting neuronal differentiation of cells within 96 ​h without added soluble differentiation factors. Our findings show that active N-cadherin binding plays an important role for differentiation of human iPS-derived neural stem cells towards neurons, providing a new tool to differentiate cells in vitro.